Positive Emotions During Infant Feeding and Breastfeeding Outcomes. (February 2020) - Wouk, Kathryn; Tucker, Christine; Pence, Brian W.; Meltzer-Brody, Samantha; Zvara, Bharathi; Grewen, Karen; Stuebe, Alison M.
Background: Few studies have examined the role of maternal emotions in breastfeeding outcomes. Research aim: We aimed to determine the extent to which positive maternal emotions during human milk feeding at 2 months were associated with time to any and exclusive human milk feeding cessation and overall breastfeeding experience. Methods: A sample of 192 women intending to breastfeed for at least 2 months was followed from the third trimester until 12 months postpartum. Positive emotions during infant feeding at 2 months were measured using the modified Differential Emotions Scale. Cox proportional hazards regression was used to estimate adjusted hazard ratios (aHR) for time to any and exclusive human milk feeding cessation associated with a 1-point increase in positive emotions. Linear regression was used to estimate the association between positive emotions and maternal breastfeeding experience reported at 12 months. Results: Among those human milk feeding at 2 months, positive emotions during feeding were not associated with human milk feeding cessation by 12 months (aHR = 0.94, 95% CI [0.64, 1.31]). However, among women exclusively human milk feeding at 2 months, a 1-point increase in positive emotions was associated with a 35% lower hazard of introducing formula or solid foods by 6 months (aHR = 0.65, 95% CI [0.46, 0.92]). Positive emotions were associated with a significantly more favorable maternal report of breastfeeding experience at 12 months. Results were similar in sensitivity analyses using maternal feelings about breastfeeding in the first week as the exposure. Conclusions: A positive maternal emotional experience of feeding is associated with breastfeeding outcomes.